RAD51 stabilizes neutrophil extracellular traps to compartmentalize inflammation. - Tsansizi,LI; Guan,SY; Aramburu,IV; Punatar,RS; Williams,TJ; Qiao,YE; Reed,A; Armstrong-James,D; West,SC; Papayannopoulos,V (Science, 2026)
Neutrophil extracellular traps (NETs) feature a branched chromatin architecture whose origin and function remain unknown. We found that NET branching is mediated by RAD51, a protein generating DNA junctions during DNA recombination repair. Pharmacological inhibition, RAD51 knockdown, or GEN1 and RuvC resolvase treatment reduced branching and destabilized NETs, whereas RAD51 up-regulation by different stimuli generated NETs with variable stability. RAD51 inhibition during murine pulmonary Aspergillus fumigatus infection dismantled NETs and reduced lung cytokines. However, the increased accumulation of NET components in the circulation led to interleukin-6 (IL-6) induction in circulating monocytes that exacerbated type 2 inflammation and asthma. Extracellular plasma DNA correlated with IL-6 and eotaxin in human aspergillosis. By structurally stabilizing NETs, RAD51 compartmentalizes inflammation to thwart aberrant systemic immune activation, linking DNA repair to inflammation.